The Effect of Online-Based Training and Work Stress on Employee Performance At PT Bank Mandiri Palembang Arief Area During The Covid-19 Pandemic - Riscahya Simbolon; Marlina Widiyanti; Muhammad Yusuf; Mohammad Adam (Institut Manajemen Wiyata Indonesia, 2022)
This study was conducted to determine the effect of online-based training and work stress on employee performance at PT Bank Mandiri Palembang Arief area during the Covid-19 pandemic. The population in this study is all employees of PT Bank Mandiri Area Palembang Arief in 2022 as many as 100 frontliner employees with sample determination using the census method (saturated sampling). Based on the results of multiple linear regression analysis that has been carried out, it shows that online-based training has a positive and significant effect on employee performance at PT Bank Mandiri Palembang area Arief during the Covid-19 pandemic. Work stress has a positive and insignificant effect on employee performance at PT Bank Mandiri Palembang Arief area during the Covid-19 pandemic. Online-based training provided to employees needs to be evaluated by the company's management in choosing the training activities provided so that the training provided can provide results / feedback that are in accordance with the company's wishes in improving employee performance. Work stress, it is necessary to have the role of superiors in providing opportunities for employees to give opinions, providing activities outside of working hours such as gatherings, eating together activities is also one of the options in order to create relationships between fellow employees and superiors can be well established. For employees, it is hoped that the company needs to evaluate again in determining the employee's work position so that the work given is easy to live and manage, besides that it can also reduce the company's costs in conducting training. If the skills and education possessed are appropriate, then there is no need to do too much training and reduce the work stress felt by employees.